Higher perceived risks of antimicrobial use are related to lower usage among pig farmers in four European countries. (12th November 2016) - Visschers, V. H. M.; Postma, M.; Sjölund, M.; Backhans, A.; Collineau, L.; Loesken, S.; Belloc, C.; Dewulf, J.; Emanuelson, U.; Grosse Beilage, E.; Siegrist, M.; Stärk, K. D. C.
Abstract : The prudent use of antimicrobials (AMs) should be widened in pig farming to reduce the risk of AM resistance (AMR) in human and veterinary medicine. It is therefore important to understand pig farmers' motivators and the barriers to AM usage (AMU) on their farms. The authors investigated pig farmers' self‐estimated levels of AMU, their perceived benefits and risks and the need for AMs in a cross‐sectional survey in Belgium, France, Germany and Sweden. The authors also compared these perceptions between the four countries and related them to pig farmers' actual AMU. The results showed that farmers who used more AMs also estimated their own usage as higher. Farmers perceived many benefits but relatively few risks of AMU in pig farming. Some significant cross‐country differences in farmers' perceptions were found, but they were relatively small. After controlling for country differences and farm differences, only perceived risks had a significant association with AMU. The authors therefore conclude that in order to promote prudent AMU, it seems most promising to focus on the structural differences in pig farming and veterinary medicine (e.g. legislation, role of the veterinarian) among countries. In addition, interventions which aim at reducing AMU should increase farmers' awareness of the risks of extensive AMU.